Non-Operatively Treated Thoracolumbar Burst Fracture with Posterior Ligamentous Complex Injury: Case Report and Consideration on the Limitation of Thoracolumbar Injury Classification and Severity (TLICS) Score - Woo-Keun Kwon; Jong-Keon Oh; Jun-Min Cho; Taek-Hyun Kwon; Youn-Kwan Park; Hong Joo Moon; Joo Han Kim (Journal of Trauma and Injury)
Fractures at the thoracolumbar region are commonly followed after major traumatic injuries, and up to 20% of these fractures are known to be burst fractures. Making surgical decisions for these patients are of great interest however there is no golden standard so far. Since the introduction of Thoracolumbar Injury Classification and Severity (TLICS) score in 2007, it has been widely used as a referential guideline for making surgical decisions in thoracolumbar fractures. However, there is still limitations in this system. In this clinical case report, we introduce a L1 burst fracture after motor vehicle injury, who was successfully treated conservatively even while she was graded as a TLICS 5 injury. A case report is presented as well as discussion on the limitations of this grading system.